Literature, freedom and the humanization of man - Camargo Abrahao, Thiago Henrique de [UNESP]; Infante, Ulisses [UNESP] (Assoc Int Lusitanistas, 2016)
Because of the gradual decrease in the historical sense of men - consciences, therefore, susceptible to the social reality, living amid fragmented values that do not allow a more complete and thorough understanding of their situation in the world. there would be, according to Jean-Paul Sartre, a function for literature, namely, to be a means to stimulate the perception of freedom and man's responsibility, demonstrating thereby the humanizing role of literary art, founded in the basis of a philosophical thought (the existentialism) which wants to be a humanism. From the Sartrean thought, we see that the Brazilian literary critic Antonio Candido's ideas on the role of literature converge for the same purposes, so that, on our part, we will underline the importance of the theoretical statements of the two thinkers to debate the present.
Keywords: literature; humanism; freedom; responsibility; Jean-Paul Sartre; Antonio Candido